Ireland : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper for Ireland highlights that fiscal consolidation resulted in a tremendous reduction in public debt from nearly 100 percent of GDP in 1991 to about 30 percent in 2004. This has reflected a combination of policy decisions and economic circumstances. Excluding 2001, when the economy has been affected by the global economic slowdown, Ireland has in general consistently enjoyed favorable surprises in its public finances. Indeed, during this period, the actual fiscal outturns have exceeded budget forecasts on average by 0.3 percent of GDP a year.